Uterine bleedings during continuous combined hormonal replacement therapy – an attempt to clinically evaluate the problem and the proposal of the management algorithm - Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2002)
The abnormal uterine bleedings during hormonal replacement therapy constitute one of the most frequent causes of the HRT discontinuation. Bleeding during continuous combined HRT is of special importance. In patients recruited and monitored according to the modern, evidence-based algorithms, bleeding during ccHRT in most cases requires only expectant management as sudden cessation of the hormonal substitution would deprive many of these patients of the multidirectional benefits of HRT.